Optimization of zeotropic series cycle for improved temperature matching and energy efficiency in compact household refrigerators - Bingqi Li; Yanjun Du; Xudong Ma; Yuting Wu; Che Wang; Jie Lin; Haiqing Guan; Lubing Wang (International Journal of Refrigeration, 2026)

When defence mechanisms fail: Multi-omics evidence of antioxidant system collapse in Thymallus grubii liver under acute temperature stress - Xinchi Shang; Xinghua Che; Kai Ma; Huaifa Chen; Lanlan Zhang; Huizhi Sun; Yanjun Li; Meiqi Xing; Wei Xu; Wenhua Wu; Yongquan Zhang (Marine Pollution Bulletin, 2026)

Temperature sensitivity and rainfall heat flux drive rapid mass loss of low-latitude glaciers in the Southeastern Qinghai–Tibet Plateau - Yanjun Che; Shijin Wang; Yun Cao; Weiwei Lv; Xinggang Ma; Congzheng Han; Jian Zhong; Rong Wu (CATENA, 2026)

Deposition characterization and predictive modeling of phosphorus and heavy metals during sewage sludge incineration - Qianqian Guo; Taojie Duan; Yanjun Hu; Long Jiao; Lingqin Zhao; Fan Yu; Xu Wang; Lei Che; Frederik Ronsse (Journal of Environmental Management, 2026)

Glacier and glacial lake evolution in response to local climate forcing: A quantitative assessment in Ulugh Muztagh, Eastern Kunlun Mountains - Lihua Chen; Yanjun Che; Yun Cao; Mingjun Zhang; Lailei Gu; Shijin Wang (Cold Regions Science and Technology, 2026)

Evaluation of the working performance of different digging shovels based on the maize root-soil complex model - Hailong Che; Hua Zhou; Zhengzhong Li; Xian Wang; Xianliang Wang; Zhongcai Wei; Yanjun Li; Yinping Zhang (Biosystems Engineering, 2025)

Enhancing acid resistance of Escherichia coli based on directed morphology evolutionary of key transcription factor bolA - Zongling Chen; Xingyu Huo; Jiali Wan; Jinming Che; Meiyi Deng; Yingnan Bao; Hailin Yang; Yanjun Tong; Shoushuai Feng (Food Bioscience, 2024)

MiR-497-5p ameliorates the oxyhemoglobin-induced subarachnoid hemorrhage injury in vitro by targeting orthodenticle homeobox protein 1 (Otx1) to activate the Nrf2/HO-1 pathway - Jun Zhu; Enyu Pan; Lujun Pang; Xiwei Zhou; Yanjun Che; Zhao Liu (Molecular Genetics and Genomics, 2024)

Enhancing column bioleaching of chalcocite by isolated iron metabolism partners Leptospirillum ferriphilum/Acidiphilium sp. coupling with systematically utilizing cellulosic waste - Xingyu Huo; Jianna Liu; Xianjing Hong; Haochen Bai; Zongling Chen; Jinming Che; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2024)

Visualization study on the flow and migration characteristics of R290/PAG oil in a room air conditioner during startup and defrosting processes - Che Wang; Jianhua Wu; Bowen Lei; Yanjun Du; Jinbo Li (International Journal of Refrigeration, 2023)

Seasonal evolution of aerosol loading and its vertical distribution in northeastern China from long-term satellite observations and model reanalysis - Hujia Zhao; Ke Gui; Yanjun Ma; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Lei Zhang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2023)

Contribution of five major apple polyphenols in reducing peanut protein sensitization and alleviating allergencitiy of peanut by changing allergen structure - Shanfeng Sun; Tianyi Jiang; Yanjun Gu; Lu Yao; Hang Du; Jiangzuo Luo; Huilian Che (Food Research International, 2023)

Rapid changes to glaciers increased the outburst flood risk in Guangxieco Proglacial Lake in the Kangri Karpo Mountains, Southeast Qinghai-Tibetan Plateau - Yanjun Che; Shijin Wang; Yanqiang Wei; Tao Pu; Xinggang Ma (Natural Hazards, 2022)

Suppression of MALAT1 alleviates neurocyte apoptosis and reactive oxygen species production through the miR-499-5p/SOX6 axis in subarachnoid hemorrhage - Xiwei Zhou; Bao Zheng; Lujun Pang; Yanjun Che; Xin Qi (Journal of Molecular Histology, 2022)

Integrated risk assessment of glacier lake outburst flood (GLOF) disaster over the Qinghai–Tibetan Plateau (QTP) - Shijin Wang; Yanjun Che; Ma Xinggang (Landslides, 2020)

Accelerated changes of glaciers in the Yulong Snow Mountain, Southeast Qinghai-Tibetan Plateau - Shijin Wang; Yanjun Che; Hongxi Pang; Jiankuo Du; Zhonglin Zhang (Regional Environmental Change, 2020)
The Yulong Snow Mountain (YSM) is a region of temperate glaciers in the southeast Qinghai-Tibetan Plateau. The present study systematically assessed the glacier changes during the past several decades using ground-based and remotely sensed observations and referencing topographic maps. The images and maps revealed that the glaciers area in the YSM retreated by 64.02% from 1957 to 2017. The length of Baishui River Glacier No. 1 decreased by 12.5 m/year during this period, whereas the front elevation of this glacier increased by 10.83 m/year. The mean annual mass balance of this glacier was at − 0.42 metre water equivalent from 1957 to 2017, and its accumulative mass balance was − 27.45 metre water equivalent. The glacier retreats of glacier area, glacier front, and mass balance in the YSM primarily resulted from the increasing air temperature. These glacier retreats not only will have a negative impact on glacier tourism in the future, e.g., the retreat or disappearance of glaciers will reduce the attractiveness of mountainous scenic spots, but also will create new opportunities for the development of local tourism, e.g., “last chance” will simulate tourists’ curiosity. Hence, the findings of our present study help to understand the mechanism between accelerated ablation of temperate glaciers and climate change in southeast regions of Qinghai-Tibetan Plateau and provide references for local tourism administrations.

Comparison of Two Air Pollution Episodes over Northeast China in Winter 2016/17 Using Ground-Based Lidar - Yanjun Ma; Hujia Zhao; Yunsheng Dong; Huizheng Che; Xiaoxiao Li; Ye Hong; Xiaolan Li; Hongbin Yang; Yuche Liu; Yangfeng Wang; Ningwei Liu; Cuiyan Sun (Journal of Meteorological Research, 2018)

Near-surface air temperature lapse rates in Xinjiang, northwestern China - Mingxia Du; Mingjun Zhang; Shengjie Wang; Xiaofan Zhu; Yanjun Che (Theoretical and Applied Climatology, 2018)

Evaluation of the tourism climate in the Hexi Corridor of northwest China’s Gansu Province during 1980–2012 - Fuxian Zhang; Mingjun Zhang; Shengjie Wang; Fang Qiang; Yanjun Che; Jie Wang (Theoretical and Applied Climatology, 2017)

Stable water isotopes of precipitation in China simulated by SWING2 models - Yanjun Che; Mingjun Zhang; Shengjie Wang; Jie Wang; Yangmin Liu; Fuxian Zhang (Arabian Journal of Geosciences, 2016)

Decrease in snowfall/rainfall ratio in the Tibetan Plateau from 1961 to 2013 - Jie Wang; Mingjun Zhang; Shengjie Wang; Zhengguo Ren; Yanjun Che; Fang Qiang; Deye Qu (Journal of Geographical Sciences, 2016)

Comparison of GCM-simulated isotopic compositions of precipitation in arid central Asia - Shengjie Wang; Mingjun Zhang; Fenli Chen; Yanjun Che; Mingxia Du; Yangmin Liu (Journal of Geographical Sciences, 2015)